Power Sharing Control Strategy in AC Microgrid System Consisting of Renewable Energy Sources - Kshatri, Abinash; Dhami, Sandeep; Bhatta, Amrit (Journal of Science and Engineering, 2025)
Addressing the need for reliable off-grid electricity in regions like Nepal, this paper investigates a power sharing control strategy for an islanded AC microgrid comprising a 60 kW micro-hydropower (MHP) unit and a 33.4 kW solar photovoltaic (PV) system. The proposed strategy employs a swing equation-based droop controller for the PV inverter to emulate synchronous generator inertia and facilitate dynamic power sharing with the MHP, which is managed by conventional governor and excitation controls. System performance was evaluated using MATLAB/Simulink under significant load variations, including a 20 kW active power step load and 5 kVAR reactive power step. The results demonstrate the system’s ability to maintain the frequency deviation within ±1% of 50 Hz and the voltage deviation within 4.9%, ensuring robust stability and effective load allocation. This research contributes to a validated control approach and detailed performance analysis for a batteryless MHP-PV hybrid configuration, offering practical insights for deploying sustainable and stable decentralized energy systems in remote geographical locations.